Dynamic visual simulation of growth and management of Chinese Fir Based on Structured Forest Management. Issue 1 (May 2020) - Kang, Shen; Tingdong, Yang; Huaiqing, Zhang; Lili, Zhang
Abstract: Based on the theory of Structure-based Forest Management, this paper studies the growth-management process of a forest considering the healthy state of the forest structure, and realizes three-dimensional visual simulation of this process based on unity3D. According to the angle scale, size ratio, crowding degree and other quantitative indexes of forest structure proposed by the theory of Structure-based Forest Management, the Spatial Structural function model and urgency management of forest were established to quantify the state of forest structure from many aspects. The growth equation of Chinese fir was fitted by the single tree growth equation based on the Hegyi competition index and forest density. Pre-thinning timbers are selected according to the rule that the cutting volume is less than the all growth volume in stand and size of competition index, and then the top 30%, 50% or 80% of pre-thinning timbers are extracted by rule sampling on the basis of pre-thinning timbers, and the stand structure function after thinning is alse calculated. The minimum value of thinning plan is taken as the actual thinning plan. Our results show that according to the growth period of 5 years, the growth and management of sample plot 5 were simulated for next 10 years. As in this case, based on the structured forest management, the dynamic visual simulation method of Chinese fir stand growth-management can realize the visual simulation of Chinese fir stand growth and management, which is a good way to show the forest growth management, and has a good demonstration role in improving the forestry informatization.